1973
DOI: 10.1002/j.2333-8504.1973.tb00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Behavior in Thirteen‐month‐old, Opposite Sex Twins

Abstract: Seventeen sets of opposite sex twins, 13 to 14 months old, were observed in a playroom situation with their mothers. Attachment behaviors, toy preference, style of play, and activity level were recorded. Analysis of four attachment behaviors indicated that girls looked at, vocalized to, and maintained proximity with their mothers significantly more often than did their brothers. Girls also touched their mothers more often, although this difference was not significant. The style of play and activity level measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…By contrast, co-twin independence appears to be associated at school with girl-boy pairs. This result is in line with the idea that mixed-sex twins are differentiated the most by their parents since early childhood, as demonstrated in several studies on dress practices (Brooks & Lewis, 1974;Goshen-Gottstein, 1981;Robin, Josse, Kheroua, Casati, & Tourette, 1994). Moreover, some studies have shown that already by preschool age, friendships are formed on the basis of sex identification (La Freniere, Strayer, & Gauthier, 1984).…”
Section: Discussionsupporting
confidence: 78%
“…By contrast, co-twin independence appears to be associated at school with girl-boy pairs. This result is in line with the idea that mixed-sex twins are differentiated the most by their parents since early childhood, as demonstrated in several studies on dress practices (Brooks & Lewis, 1974;Goshen-Gottstein, 1981;Robin, Josse, Kheroua, Casati, & Tourette, 1994). Moreover, some studies have shown that already by preschool age, friendships are formed on the basis of sex identification (La Freniere, Strayer, & Gauthier, 1984).…”
Section: Discussionsupporting
confidence: 78%
“…These findings were very similar to those of Savic (1980), who found that twins came to use possessives sooner and more frequently than singletons and who interpreted these data as a more rapid movement through the steps of using 'I' and a sign of a strong motivation to be differentiated. Incidentally such precocious indices of self-awareness allow us to revisit the prevalent claim that twins' mothers do not scaffold an early access to self-other differentiation within the twin dyad (Brooks & Lewis 1974, Goshen-Gottstein 1981, Lytton 1980, Lytton, Conway & Sauve 1977, Robin, Corroyer & Casati 1996). Rather, our results are better understood in the light of Clark & Dickman's (1984) description of the twins' mother who rarely maintained her attention on one twin because she very frequently shifted her visual attention to the co-twin.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that monozygotic twins are treated in a more similar fashion than dizygotic twins (Loehlin & Nichols, 1976;Cohen, Dibble & Grawe, 1977). The greatest difference exists in the case of different-sex twins, and mothers of such twins can be expected to find it easier to treat the children as two distinct individuals (Brooks & Lewis, 1974;Goshen-Gottstein, 1981).…”
mentioning
confidence: 98%